PHENOMENOLOGY OF DELUSIONS AND HALLUCINATIONS IN SCHIZOPHRENIA IN CENTRAL PUNJAB, PAKISTAN - Sajid, Wahid Bakhsh; Rashid, Shahid; Akhtar, Farrukh (Pakistan Armed Forces Medical Journal, 2011)
Objective: To examine the variations in the frequency and contents of delusions and hallucinations in schizophrenia and correlates the significant findings with other studies across culture. Study Design: Case series study Place and Duration of Study: Psychiatry Department CMH Kharian for four year duration. Material and Methods: Eighty consecutive patients of schizophrenia (62 men and 18 women) were registered and evaluated for frequency of different delusions and hallucinations. The patients belonged to central Punjab (Pakistan). DSM-IV diagnostic criteria were used for diagnosis. Results: Most patients i.e. 72.25% belonged to lower social class. Auditory hallucinations were the commonest (81.25%) followed by tactile hallucinations (14.75%) and visual hallucinations (7.5%). Delusions of persecution were found in very high percentage (91.25%) delusions of reference in 42.5% and delusions of control in 31.25%. The patients believed that they were influenced by magic, demons and pirs. First rank symptoms of schizophrenia were present in 76.25% of patients; made affect, made impulse and made volition were present in (40.8%) and somatic passivity were present in (18%) of cases. Conclusion: Sociocultural background of the patients is likely to contribute in shaping the phenomenology of delusions and hallucinations and it is recommended that more elaborate/different diagnostic criteria may be designed for diagnosis of schizophrenia in developing countries.